1984
DOI: 10.1093/jac/14.5.521
|View full text |Cite
|
Sign up to set email alerts
|

Serum and sputum concentrations of ceftazidime in patients with cystic fibrosis

Abstract: The pharmacokinetic parameters of ceftazidime were assessed in six cystic fibrotic patients during eight courses administered for acute exacerbations of pulmonary infection. In order to assess the initial and steady state concentrations of ceftazidime at a dose of 35 mg/kg and to determine the levels found after a higher dose, each ten day course of ceftazidime consisted of eight doses of 35 mg/kg followed by 22 doses of 50 mg/kg, all administered at 8-hourly intervals. Samples of blood and sputum were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A number of studies of other drugs have demonstrated that patients with CF frequently display different PK parameters compared to patients without CF (e.g., Cl, Vd) . In our analysis, we found similar overall PK parameter estimates between both patient populations when using NCA.…”
Section: Discussionsupporting
confidence: 70%
“…A number of studies of other drugs have demonstrated that patients with CF frequently display different PK parameters compared to patients without CF (e.g., Cl, Vd) . In our analysis, we found similar overall PK parameter estimates between both patient populations when using NCA.…”
Section: Discussionsupporting
confidence: 70%
“…Our results on terminal half-life (Table 2) were in good agreement with the shorter terminal half-life of 1.5 Ϯ 0.2 h in CF patients compared to 1.76 Ϯ 0.2 h in healthy volunteers reported by Leeder et al (44). The reported average half-lives in juvenile to adult CF patients range between 1 and 2 h (41,47,50,56,58,68,72,76).…”
Section: Discussionmentioning
confidence: 99%
“…Ceftazidime and tobramycin concentrations in serum and in sputum were determined by high performance liquid chromatography (HPLC) using modifications of previously described methods. 16,17 Bacterial Isolation and Susceptibility Testing Bacteria were cultured from the sputum samples collected from patients on admission to hospital, prior to commencing antibiotic treatment. The sputum samples were liquefied by incubation with sputolysin for 15 min and serial tenfold dilutions prepared in sterile phosphate buffered saline.…”
Section: Analytical Methodologiesmentioning
confidence: 99%